PREVALENCE OF TONGUE DISEASES IN CHILDREN TREATED AT DENTAL CLINICS IN THE UNIVERSITY OF CARTAGENA (Revista Nacional de Odontología, 2014)
Introduction: Tongue diseases can affect the oral mucosa of the child, so the dentist is responsible of his detection by a routine semiological examination. The goal of this study is derived from the research, “The prevalence of tongue diseases in children treated at dental clinics” in the Universidad de Cartagena (University of Cartagena) from 1999 to 2009´.Materials and methods: A retrospective-descriptive analysis; sample showed 297 randomly selected medical records in 2010. We evaluated the pathology presence, classification and demographic features. Absolute and relative frequency distributions were used with confidence intervals of 95%. For bivariate analysis x² statistical test was used, assuming a significance limit of 0.05.Results: The prevalence of tongue diseases was 39.4%, most frequently diagnosed lesions were coated tongue 32.7%, tongue tie 5.7%, benign migratory glossitis 1.7%, and fissured tongue 0.7%.Conclusion: Tongue pathologies in children are highly predominant, being the most frequently coated tongue. Therefore, we must implement management protocols to encourage children and parents healthy oral hygiene behaviors by emphasizing brushing the dorsal tongue surface.
Keywords: tongue diseases; benign migratory glossitis; fissured tongue; prevalence.